(untitled) (Health and Biosciences, 2026)
Nickel chloride (NiCl₂) is an environmentally abundant heavy metal known to induce oxidative stress, metabolic disturbances, and hepatocellular injury. Identifying natural hepatoprotective agents remains crucial for mitigating heavy-metal toxicity. Telfairia occidentalis fruit contains rich phytochemicals with reported antioxidant and therapeutic properties. To evaluate the protective effects of aqueous Telfairia occidentalis fruit extract against NiCl₂-induced hepatic toxicity in Wistar rats. Twenty-four Wistar rats were divided into four groups (n = 6): Control, NiCl₂ (5 mg/kg, i.p.), T. occidentalis fruit extract (200 mg/kg p.o.) + NiCl₂ (pre-treated 1 hour before NiCl₂), and extract-only group (200 mg/kg p.o.). Treatments lasted 28 days. Body weight, relative liver weight, serum liver enzymes, oxidative stress biomarkers (MDA, GSH, SOD, CAT), and histopathology (H&E) were assessed. Data were analysed using ANOVA with Tukey’s post-hoc test at p < 0.05. NiCl₂ exposure caused significant reductions in body weight, increased liver enlargement, elevated serum AST, ALT, ALP, increased MDA, and depleted antioxidant defences. Histology revealed periportal fibrosis, inflammation, hepatocyte vacuolation, and sinusoidal congestion. Pre-treatment with T. occidentalis fruit extract markedly improved body weight, reduced liver enlargement, stabilised liver enzymes, restored antioxidant biomarkers, and preserved hepatic microarchitecture. Extract-only rats showed normal hepatic and biochemical integrity. Aqueous Telfairia occidentalis fruit extract demonstrates significant hepatoprotective, antioxidant, and membrane-stabilising effects against NiCl₂-induced liver toxicity. The fruit possesses therapeutic potential for mitigating heavy-metal-related hepatic damage, supporting its relevance as a natural protective agent.